Application of petrophysical shale gas model for CO2 storage capacity assessment of coals. (July 2018) - Lutynski, Marcin; Zavanella, Lucio
Abstract: Carbon dioxide storage in unmineable coal seams is a potential solution for the reduction of GHG emissions. For the purpose of storage capacity estimations various static and dynamic models are applied and in this study a simple petrophysical model, originally designed for shale gas reservoirs, has been used. This model comprises of volumetric (free gas) and surface (adsorbed gas) component. Important input data for the model are Langmuir constants and other reservoirs parameters such as water saturation, porosity and rock density. Sorption isotherms on two distinct coals from the Upper Silesia Coal Basin were measured and calculated Langmuir constants with typical reservoir parameters were implemented into the model. It occurred that coal with higher ash content and higher sorption capacity for methane had a lower carbon dioxide sorption capacity. This was reflected in the overall carbon storage capacity which for the two coals varied from 31 m 3 /t to approximately 42 m 3 /t of coal at the storage pressure of 5.5-6 MPa where the majority of stored gas is the surface component (sorbed gas).